Empowerment of Farmer Group in Controlling Spodoptera frugiperda on Corn Using Entomopathogenic Fungi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Raden Farmer Group is one of the farmer groups in Pabuwaran, Purwokerto District, Banyumas Regency. This group faced the problem of encountering the attack of Spodoptera frugiperda on corn. This pest caused a detrimental loss in corn cultivation. The common control technique used to control this pest is by applying chemical insecticides. The use of this chemical insecticide causes negative effects on both the environment and human health. The offered solution to overcome this problem is technology transfer using entomopathogenic fungi, which is environmentally safe. Technology transfer was conducted through mentoring, education, and demonstration plots (demplots).Evaluation was carried out by pre-test and post-test for each activity to find out how well the partners understood the presented materials. The improvement in skills was measured by assessing the entomopathogenic fungi-based bioinsecticide product that was successfully made in the training activity by the partners, the decrease in S. frugiperda attack intensity, and the increase in yields in demplot. The evaluation results showed: (a) improvement of the partner’s knowledge and skills regarding S. frugiperda and its control technique using entomopathogenic fungi; (b) the results on demplot showed that the use of entomopathogenic fungi could replace the application of chemical insecticides to control S. frugiperda. (c) Farm analysis showed that the use of entomopathogenic fungi in corn cultivation was efficient and profitable for farmers.